Complementary Therapy for Hypertension Control: Family Medicine Therapy and Tai Chi Gymnastics in the Community of Nengkelan Village, Bandung Regency - Sinaga, Herwinda; Natalia, Lidya; Maryani, Lidya; Melia, Stephanie (CV Media Inti Teknologi, 2024)
The purpose of community service is to provide new insights into a holistic approach to hypertension control and improve the quality of life of village communities through complementary therapy that combines Tai Chi gymnastics and family medicine therapy. This community service activity was implemented in Nengkelan Village, Bandung Regency. The activity lasted for 1 week. The stages of this activity consist of preparation, implementation, and evaluation. The results of a study in Nengkelan Village, Bandung Regency, showed that combining family medicine therapy with Tai Chi gymnastics can be an effective method to control hypertension. The use of complementary strategies that combine medical and non-medical therapies can have a positive impact on hypertension control in the community. Complementary therapy, which consists of family medicine therapy and Tai Chi gymnastics, is effective in controlling hypertension in the people of Nengkelan Village, Bandung Regency. The implementation of this therapy in the community can be one of the solutions to overcoming the problem of hypertension holistically and improving the quality of life of hypertension patients.